The Adsorption of Phenol, -Cresol and -Catechol on a β-Cyclodextrin Derivative-Grafted Chitosan and the Removal of Phenols from Industrial Wastewater - Qi Yuan Chen; Jian Bo Xiao; Xiao Qing Chen; Xin Yu Jiang; Hong Zhu Yu; Ming Xu (Adsorption Science & Technology)
A β-cyclodextrin derivative (CCDC) was synthesized with chitosan and carboxymethyl-β-cyclodextrin, and its structure was characterized via elemental analysis, infrared spectral analysis and X-ray diffraction analysis. On addition of DMF to the reaction solution, the degree of substitution by the carboxymethyl-β-cyclodextrin moiety achieved a value of 0.27. The results were in agreement with expectations. The static adsorption properties of CCDC towards phenol, m -cresol and m -catechol were studied. The experimental results demonstrated that CCDC had a higher adsorption capability towards m -catechol than for phenol and m -cresol, with the adsorption capacity for m -catechol being 110.56 mg/g. The adsorption capacity was greatly influenced by the pH, time and temperature. The introduction of chitosan enhanced the adsorption ability and adsorption selectivity of β-cyclodextrin towards m -catechol. This novel chitosan derivative demonstrated high percentage removal of phenols from wastewater.